Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Inverse high internal phase emulsion polymerization (i-HIPE) of GMMA, HEMA and GDMA for the preparation of superporous hydrogels as a tissue engineering scaffold - Nalawade, Archana C.; Ghorpade, Ravindra V.; Shadbar, Sadiqua; Qureshi, Mohammed Shadbar; Chavan, Nayaku; Khan, Ayesha A.; Ponrathnam, S. (Journal of Materials Chemistry B, 2016)
A series of novel superporous hydrogels for regenerative medicine were prepared by oil-in-water (o/w) or inverse high internal phase emulsion (i-HIPE) copolymerization of glycerol monomethacrylate (GMMA), 2-hydroxy ethyl methacrylate (HEMA) and glycerol dimethacrylate (GDMA) as a cross-linker using a non toxic solvent and a redox initiator system at the physiological temperature (37 degrees C). The monomer GMMA was synthesized from glycidyl methacrylate (GMA) by an alternative facile method using Amberlyst-15. The described i-HIPEs showed a significantly wider stability window. The polyHIPE hydrogels were characterized by FTIR, BET method for surface area, mercury porosimetry, SEM, DSC, TGA, XRD, compressive strain and strain recovery. The swelling ratio of the hydrogels and their degradation in 0.007 M NaOH and lipase B (Candida antarctica) solutions were determined gravimetrically and the rate of degradation was explained in terms of the molecular structure of the hydrogels. The morphological studies showed that the pore diameter varied between 20 and 30 mu m and the pore throats (interconnecting windows) diameter was in the range of 4-8 mu m. The described polyHIPE hydrogels were found to have an open cell morphology and interconnected pore architecture, which are important characteristics for scaffold applications. The initial cytotoxicity study performed according to ISO-10993-5 indicated cytocompatibility (97% cell viability) and the subsequent cell seeding and proliferation study exhibited 55-88% cell viability (increased monotonously from GHG-1 to GHG-5), which could be attributed to modulation of the physical and chemical properties of the hydrogels. The described super porous hydrogels are considered as potential candidates for scaffold materials in tissue engineering applications.

Electrochemical capacitive energy storage in PolyHIPE derived nitrogen enriched hierarchical porous carbon nanosheets - Deshmukh, Ashvini B.; Nalawade, Archana C.; Karbhal, Indrapal; Qureshi, Mohammed Shadbar; Shelke, Manjusha V. (Carbon, 2018)
Porous and interconnected electrodes based on carbon nanoarchitectures offer comprehensive advantages of large specific surface area and high porosity consequently increasing the specific capacitance of ultracapacitor energy storage systems. Emulsion-templated polymers, PolyHIPEs (Polymerized High Internal Phase Emulsions) are highly porous polymers with a structure of cages interconnected by windows thus provide suitable framework to create such porous carbon nanostructures. Herein, nitrogen enriched porous carbon nanosheets are synthesized by pyrolysis of polymer-silica hybrid PolyHIPE and subsequent silica removal. This nitrogen enriched porous carbon nanosheets when tested as an electrode for ultracapacitor, showed specific capacitance as high as 209 F/g at a current density of 1 A/g in 1 M H2SO4 with excellent capacity retention over long cycling. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Energy storage; Nitrogen enriched porous carbon nanosheets; PolyHIPE template; Ultracapacitor